Patterns and Dynamics of Dissolved Organic Carbon (DOC) in Boreal Streams: The Role of Processes, Connectivity, and Scaling - Laudon, Hjalmar; Berggren, Martin; Ågren, Anneli; Buffam, Ishi; Bishop, Kevin; Grabs, Thomas; Jansson, Mats; Köhler, Stephan (Ecosystems (New York), 2011)
We bring together three decades of research from a boreal catchment to facilitate an improved mechanistic understanding of surface water dissolved organic carbon (DOC) regulation across multiple scales. The Krycklan Catchment Study encompasses 15 monitored nested research catchments, ranging from 3 to 6900 ha in size, as well as a set of monitored transects of forested and wetland soils. We show that in small homogenous catchments, hydrological functioning provides a first order control on the temporal variability of stream water DOC. In larger, more heterogeneous catchments, stream water DOC dynamics are regulated by the combined effect of hydrological mechanisms and the proportion of major landscape elements, such as wetland and forested areas. As a consequence, streams with heterogeneous catchments undergo a temporal switch in the DOC source. In a typical boreal catchment covered by 10-20% wetlands, DOC originates predominantly from wetland sources during low flow conditions. During high flow, the major source of DOC is from forested areas of the catchment. We demonstrate that by connecting knowledge about DOC sources in the landscape with detailed hydrological process understanding, an improved representation of stream water DOC regulation can be provided. The purpose of this study is to serve as a framework for appreciating the role of regulating mechanisms, connectivity and scaling for understanding the pattern and dynamics of surface water DOC across complex landscapes. The results from this study suggest that the sensitivity of stream water DOC in the boreal landscape ultimately depends on changes within individual landscape elements, the proportion and connectivity of these affected landscape elements, and how these changes are propagated downstream.